The Role of Folklore in the Moral and Aesthetic Upbringing of the Individual - X., Babamuradova L. (Research Parks Publishing LLC, 2022)
The theme of the article is very relevant with today as the education of morality in a person with the help of folklore gives a good effective result. Folk art, which originated deeply in antiquity, contributes to the development of figurative thinking, enriches speech. The logical conclusion is that in the moral and aesthetic education of the individual, the role of folklore is of overriding importance. Folklore is a source of education.